PERFORMA ITIK TEGAL JANTAN FASE GROWER YANG DIBERI TEPUNG DAUN ASAM GELUGUR (GARCINIA ATROVIRIDIS) DALAM RANSUM NON KONVENSIONAL TERFERMENTASI - EkoPrasetyo, fiqy; Kardaya, Dede; Dihansih, Elis (Jurnal Peternakan Nusantara, 2022)
Ducks are a type of poultry that can be utilized and developed by the People of Indonesia. Feed is a supporting fakor in livestock growth. Gelugur acid plant (Garnicia atroviridis) has the content of active substances in the form of carbohydrates and proteins as well as organic acids such as tartaric acid, citric acid, and also malat acid. Research on the effect of gelugur acid leaf flour in non-conventional fermented rations on the performance of tegal ducks. The study was 24 years old and 2 weeks old. This study using Complete Random Design (RAL) consisted of 4 treatments and 3 replays, each unit consisting of 2 male tegal ducks. Research treatment using gelugur acid leaf flour with percentage R1=0% (Control), R2=2%, R3=4%, R4=6%. The results showed the best performance shown in R3 treatment (100% ration + 4% gelugur sour leaf flour) i.e. with a consumption value of 3945.73 gram/tail/week, UN at 479.16 gram/tail/week, ration conversion of 8.26 and duck mortality rate of 0% or absence of death during maintenance. The administration of acidic leaf flour as much as 4% is the best.